2010
DOI: 10.1136/hrt.2010.203190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of restrictive physiology on intrinsic diastolic right ventricular function and lusitropy in children and adolescents after repair of tetralogy of Fallot

Abstract: Diastolic RV stiffness of repaired ToF patients with restrictive physiology is increased. The lusitropic response of the RV to β adrenergic agents is abnormal after ToF repair regardless of whether restrictive physiology is present or not. This has potential implications, particularly for postoperative drug management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…These findings are consistent with a recent combined invasive conductance catheter and cardiac MRI study in adolescents and young adults after TOF repair. 5 Using pressure-volume loop analysis, it was shown that the slope of the end-diastolic pressure-volume relationship is higher in patients with EDFF, suggesting decreased RV compliance and increased RV stiffness. 5 No differences in early relaxation parameters between the two groups could be found, because the time constant of early relaxation (t) and the maximal rate of diastolic pressure decay (dP/dt min) did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with a recent combined invasive conductance catheter and cardiac MRI study in adolescents and young adults after TOF repair. 5 Using pressure-volume loop analysis, it was shown that the slope of the end-diastolic pressure-volume relationship is higher in patients with EDFF, suggesting decreased RV compliance and increased RV stiffness. 5 No differences in early relaxation parameters between the two groups could be found, because the time constant of early relaxation (t) and the maximal rate of diastolic pressure decay (dP/dt min) did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Early after TOF repair, RV restriction results in elevated systemic venous pressures (often associated with prolonged pleural effusions or ascites) and reduced cardiac output, resulting in prolonged intensive care unit stay. 2,[4][5][6] Late after repair, the effects of restrictive RV physiology on patients' clinical status is more controversial. In adult patients late after TOF repair, restrictive RV physiology was described to be beneficial because it limits pulmonary regurgitation, resulting in less RV dilation and better exercise capacity.…”
mentioning
confidence: 99%
“…The authors considered that this may be related to a reduced myocardial perfusion reserve and impaired right ventricular systolic function (41). A report on the impact of restrictive physiology on right ventricular function after repair of tetralogy found that diastolic right ventricular stiffness was increased (42). However, the lusitropic response to b adrenergic agents was abnormal regardless of restrictive physiology.…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
“…41 A report on the impact of restrictive physiology on right ventricular function after repair of tetralogy found that diastolic right ventricular stiffness was increased. 42 However, the lusitropic response to b-adrenergic agents was abnormal regardless of restrictive physiology. In an investigation of 29 asymptomatic children with repaired tetralogy, 43 despite moderate right ventricular dilatation and right bundle branch block compared with controls, the authors demonstrated neither right ventricular nor left ventricular dyssynchrony at rest but exercise-induced mechanical dyssynchrony.…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%